Pengaruh Pemberian Kredit Usaha Mikro terhadap Potensi Pengembangan Usaha Nasabah Pegadaian Syariah Pekanbaru: The Effect of Providing Micro Business Credit on the Business Development Potential of Pekanbaru Sharia Pawnshop Customers - Zulfa, Marina (STAI Terpadu Yogyakarta, 2024)
Sharia pawnshops provide an alternative to obtain sources of funds and financing to meet financial needs. One of the products they offer is called